Perempuan dan Spiritualitasnya Dalam Perspektif Hadis - Suryadi, Suryadi (Musawa Jurnal Studi Gender dan Islam, 2008)
It has been widely known that Islam is often portrayed as a religion which marginalizes and discriminates against women. This image comes from gender-biased practices of Muslim communities in some parts of the world. The author argues that if we go deeply to the authentic teachings of Islam, be they ones based on the Qur'an and Hadith, we will certainly find many riwayah that promote equality between men and women. With regard to the issue of spirituality, this article focuses on the hadith perspective, and concludes that the Prophet Muhammad had indeed provided wide space for women (as well as mean) to exercise spirituality in order to attain highest state of purity in the eyes of Allah. Both in doctrinal and practical level never did the Prophet single out one sex against the other. There is no proof whatsoever that the Prophet discriminated women from engagi,ng in spirituality.